2022
DOI: 10.1101/2022.05.10.491402
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A long non-coding RNA is a key factor in the evolution of insect eusociality

Abstract: SUMMARYInsect sociality is a major evolutionary transition based on the suppression of worker reproduction in favor of the reproductive monopoly of the queen. In the honey bee (Apis mellifera) model organism, the development of the two female caste phenotypes, queen and worker, is triggered by differences in their larval diets. However, the mechanistic details underlying their respective developmental trajectories, as well as the maintenance of sterility in the adult workers, are still not fully understood. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 86 publications
(151 reference statements)
0
2
0
Order By: Relevance
“…Previous studies have identified several lncRNAs in honey bees 32 36 , including Nurse bee brain-selective gene-1 ( Nb-1) 35 . Recent genome-wide transcriptome analyses have comprehensively identified many lncRNAs in honey bees 37 41 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified several lncRNAs in honey bees 32 36 , including Nurse bee brain-selective gene-1 ( Nb-1) 35 . Recent genome-wide transcriptome analyses have comprehensively identified many lncRNAs in honey bees 37 41 .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, research on the function and mechanism of lncRNA is mainly focused on a few model organisms such as humans [11][12][13]. Although the transcriptomic analysis of honeybees provides insights into potential gene regulatory networks [17][18][19], only a few specific genes exhibit functional characteristics [23]. The functional aspects and mechanisms of lncRNA in bees remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%